[Crowd in University Union plaza listening to speaker on stage?] (1995)
A crowd of people is paying attention to something not visible in the photograph, possibly a speaker who is on the University Union plaza stage. A banner with a small rainbow logo and the words 'NCF: Newman Catholic Fellowship' is hung up on the second floor of the bookstore.